Cytotoxicity and reactive oxygen species production induced by different co-monomer eluted from nanohybrid dental composites - En-Shi Jiang; Wonjoon Moon; Bum-Soon Lim; Juhea Chang; Shin Hye Chung (BMC, 2023)
Abstract Background Safety issues for dental restorative composites are critical to material selection, but, limited information is available to dental practitioners. This study aimed to compare the chemical and biological characteristics of three nanohybrid dental composites by assessing filler particle analysis, monomer degree of conversion (DC), the composition of eluates, and cytotoxicity and reactive oxygen species (ROS) production in fibroblasts. Methods Three nanohybrid composites (TN, Tetric N-Ceram; CX, Ceram X Sphere Tec One; and DN, DenFil NX) were used. The size distribution and morphology of the filler particles were analysed using scanning electron microscopy (n = 5). The DC was measured via micro-Raman spectroscopy (n = 5). For the component analysis, methanol eluates from the light-polymerised composites were evaluated by gas chromatography/mass spectrometry (n = 3). The eluates were prepared from the polymerised composites after 24 h in a cell culture medium. A live/dead assay (n = 9) and Water-Soluble Tetrazolium-1 assay (n = 9) were performed and compared with negative and positive controls. The ROS in composites were compared with NC. Statistical significance in differences was assessed using a t-test and ANOVA (α = 0.05). Results Morphological variations in different-sized fillers were observed in the composites. The DC values were not significantly different among the composites. The amounts of 2-hydroxyethyl methacrylate (HEMA) were higher in TN than DN (p = 0.0022) and triethylene glycol dimethacrylate (TEGDMA) in CX was higher than in others (p < 0.0001). The lowest cell viability was shown in CX (p < 0.0001) and the highest ROS formation was detected in TN (p < 0.0001). Conclusions Three nanohybrid dental composites exhibited various compositions of filler sizes and resin components, resulting in different levels of cytotoxicity and ROS production. Chemical compositions of dental composites can be considered with their biological impact on safety issues in the intraoral use of dental restorative composites. CX with the highest TEGDMA showed the highest cytotoxicity induced by ROS accumulation. DN with lower TEGDMA and HEMA presented the highest cell viability.